Is MOOC really effective? Exploring the outcomes of MOOC adoption and its influencing factors in a higher educational institution in China - Hao Huang; Dandan Qi (PLoS ONE, 2025)
Massive Open Online Course (MOOC) has gained widespread adoption across diverse educational domains and plays a crucial role in advancing educational equality. Nevertheless, skepticism surrounds the effectiveness of MOOC due to their notably low completion rates. To explore the outcomes of MOOC adoption in higher education and improve its application efficiency, this study compares MOOC with traditional course in terms of mean score and pass rate. The study examines the factors influencing MOOC performance within the context of higher education, utilizing the method of Partial Least Squares-Structural Equation Modeling (PLS-SEM). This study analyzed MOOC learning data from a college over a period of six years and a total of 4,282 Chinese college students participated in this study. The factor of learning environment was proposed for the first time, and it was proved to have a significant impact on learning behavior and MOOC performance in higher education. The results reveal that 1) MOOC has a lower pass rate than traditional course (including both compulsory and selective course); 2) MOOC has a lower mean score than selective course only; 3) we did not find a significant difference between MOOC and compulsory course in terms of the mean score; 4) Learning behavior, learning motivation, perceived value, learning environment, previous experience and self-regulation have significant and positive influences on MOOC performance in higher education. The study provides valuable insights that college administrators should pay attention to students’ learning environment, learning motivation and other factors while actively introducing MOOC.